FAKTOR YANG MEMPENGARUHI KEPUASAN PENGGUNA SITUS BELANJA - Yudi Wahyu Wibowo (Jurnal Ilmiah Matrik, 2020)
Satisfaction is one sign of the success of a product or service in this case in the form of online shopping sites. Satisfaction assessed if users feel the achievement of a goal from the user. This study aimed to analyze the influence of variables contained in an online shopping website that quality systems, quality of information, perception of usefulness, ease of use to the user satisfaction. This research used experimental methods and quantitative data in the form of a questionnaire. The results showed that the three hypotheses were rejected and 4 received. Results of the data analysis using methods DeLone and McLean combined with Technology Acceptance Model (TAM) and PLS SEM showed that the three factors that influence user satisfaction is the quality of the system, perceived ease of use and perceived usefulness.